Influence of Teacher Trainings Organized By Quality Assurance and Standards Officers on Students’ Academic Performance in Public Secondary Schools in Gucha Sub-County, Kenya - David Ogega; George Ogochi (IJRDO- Journal of Educational Research, 2020)
The priority of learning institutions is to ensure equitable access and improvement in quality and efficiency at all levels of education. The ultimate goal is to develop an all-inclusive and quality education that is accessible and relevant to all Kenyans. However, developing standards in education and maintaining the desired quality remains a major challenge across education systems throughout the world. This study sought to conduit the existing gap of knowledge on the Influence of QAS Practices on academic performance in public school in Gucha Sub - County, Kenya. The researcher adopted a descriptive survey research design. The target population for this study was 62 head teachers and 1376 teachers in public secondary schools. In addition, the Quality Assurance and Standards Officers (QASOs) of Gucha Sub-County was also targeted in the study. The total sample size consisting of head teachers, teachers and the QASO was 313 persons. Data collection tools comprised of questionnaires, interview and observation schedule. Quantitative data was analyzed and presented in frequency tables, graphs and charts. Qualitative data was analyzed through reporting themes and quotations that emerged. The themes emerging from qualitative data were identified to augment the primary data. The findings of the study established that teacher trainings, school curriculum inspection, physical facilities inspection and stakeholder perception positively and significantly influence academic performance of students. The study recommended that the Government should organize regular in service training and workshops as they mentor teacher who in return will contribute positively to academic performance of the students. The government should invest in the physical facilities as the study has shown that they contribute positively to the performance of the student. Stakeholders should be sensitized on the activities of QASO’s and why they do inspection so as they can have a positive attitude toward the exercise.